Addition of 5% Saccharide Isomerates in Moisturizing Formulation Increases Skin Hydration Higher than Regular Moisturizers - Dian Andriani Ratna Dewi; Wimpie Pangkahila (Eduvest - Journal of Universal Studies, 2022)
Dry skin is a problem for millions of people and often causes discomfort and even psychological stress. Increasing the water content in the stratum corneum can be done by applying moisturizer regularly and regularly because it will improve lipid levels and hydrate the epidermis. Saccharide isomers (SI) are one of the answers for the development of Glycobiology. The hypothesis of this study is that the addition of 5% SI in the moisturizing formulation further increases skin hydration and can maintain higher skin hydration even after discontinuation of use compared to ordinary moisturizers. The research subjects were 30 women aged 30-45 years who were not menopausal. Randomly divided into control group (15 people) and treatment group (15 people) by double blind. Moisturizer used for 2 weeks in a row, then discontinued use. Measurement of skin hydration was carried out 3 times a week during the use of moisturizer and after discontinuation. The non-invasive measuring instrument used is the Multi Skin Test Center® MC 750 made in Germany. Giving moisturizer in both groups resulted in an increase in skin hydration after 2 weeks of use (p<0.05). After discontinuation of the moisturizer, the four locations showed significant differences in skin hydration (p<0.05). From the results of this study, it can be concluded that the addition of 5% SI in the moisturizing formulation can increase skin hydration higher and can maintain higher skin hydration even after discontinuation of administration compared to ordinary moisturizers.